Handling Money: Credit Use - Mary N. Harrison (EDIS)
Credit is one of the most important resources available to you. Used wisely, credit will enable you to have a good quality of life. Misused, it will destroy your quality of life. Unfortunately many people do not know how to shop for and use credit wisely. This document is FCS5235-02, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.